PSYCHOLOGICAL AND PEDAGOGICAL READINESS OF STUDENTS FOR PROFESSIONAL ACTIVITIES IN AN INCLUSIVE ENVIRONMENT - Khilya, Anna; Kolosova, Olena; Sarancha, Irina; Kazmirchuk, Natala (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In this article, we analyze the modern approaches to the formation of the educational policy of the state of Ukraine on inclusion issues; we partially touch upon the issues of teaching “normotypical” children, children with special educational needs (as defined in the legislation of Ukraine), and “normotypical” children with “situational deviations”. Based on the analysis of the processes of perception and implementation of inclusion in the educational environment, we consider the process of training future specialists using democratic training methods. With the help of such methods, we introduce, as an element of preparation, students' self-development and self-awareness of themselves as individuals who are ready for “open” questions, democratic dialogue. We believe that this is an indicator of the teacher’s professional readiness to “accept” children with special educational needs.The main methods of our research are a theoretical analysis of inclusive education issues, preparing students for work in a “democratic” school; observation, conversation, questionnaires, study of the experience of preparing students for work in an inclusive education.As a result, we highlighted the organizational and pedagogical conditions that allow to: increase the level of professional readiness of students; create the most favorable conditions for the development of inclusive education.